A Study on Buying Behavior of Consumer towards Online Shopping With Reference to Bangalore City - S N, Mrs. Lakshmi; V, Mrs. Indumathi (The journal of contemporary issues in business and government, 2022)
On-line shopping is a recent phenomenon in the field of E-Business and is definitely going to be the future of shopping in the world. Most of the companies are running their on-line portals to sell their products/services on-line. Though online shopping is very common outside India, its growth in Indian Market, which is a large and strategic consumer market, is still not in line with the global market. This new shopping technique is innovative in nature. As compared to traditional way of doing shopping, it not just brings an incredible number and extensive variety of stock to the purchasers; additionally offers a far reaching market and endless business opportunities. The data was collected through Questionnaires on a sample of 580 respondents from Bangalore City. Simple random sampling method has been used for data collection. Both primary data and secondary data has been collected for this study